Gender equality and the human rights of women and girls as sustainable development goals - Analía Consolo; Erika Bauger (Oñati Socio-Legal Series)
The current situation of women and girls has worsened, this is clearly showed in the objectives of the Schedule of 2030 for sustainable development of the United Nations, which indicates that with the pandemic the actions taken to achieve better standards have been receding. The case of women who are migrant, refugees or displaced from their homes, many of them victims of inhuman treatment and repeated violations. In this article we put special emphasis on the relationship and constant articulation of international normative instruments in the field of Human Rights and Private International Law in order to find possible answers to the problems that arise, from a gender perspective.